A discrete domain of the human TrkB receptor defines the binding sites for BDNF and NT-4. - Naylor, R; Robertson, A; Allen, S; Sessions, R; Clarke, A; Mason, G; Burston, J; Tyler, S; Wilcock, G; Dawbarn, D (2002)
TrkB is a member of the Trk family of tyrosine kinase receptors. In vivo, the extracellular region of TrkB is known to bind, with high affinity, the neurotrophin protein brain-derived neurotrophic factor (BDNF) and neurotrophin-4 (NT-4). We describe the expression and purification of the second Ig-like domain of human TrkB (TrkBIg(2)) and show, using surface plasmon resonance, that this domain is sufficient to bind BDNF and NT-4 with subnanomolar affinity. BDNF and NT-4 may have therapeutic implications for a variety of neurodegenerative diseases. The specificity of binding of the neurotrophins to their receptor TrkB is therefore of interest. We examine the specificity of TrkBIg(2) for all the neurotrophins, and use our molecular model of the BDNF-TrkBIg(2) complex to examine the residues involved in binding. It is hoped that the understanding of specific interactions will allow design of small molecule neurotrophin mimetics.